Private initiative for groundwater recharge: case of Dudhada village in Saurashtra - Sakthivadivel, Ramaswamy; Nagar, R.K. (International Water Management Institute, 2003)
Research highlight based on a paper titled ?Response to provate initiative for water recharge: Case of Duhada Village, Amreli District?